Punggawa authority and its Sawi compliance during the Covid-19 Pandemic (Case study on Beba Fishing Community, Takalar Regency) - Arisnawawi Arisnawawi; Darmawan Salman; Rahmat Muhammad; Muhammad Sabiq (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
The beating of fishermen due to the Covid-19 pandemic does not necessarily damage the Punggawa-Sawi relationship in Beba, Takalar Regency. The obedience of the Sawi people in choosing to stay with the Punggawa must be photographed from a different angle. This relationship can no longer be seen as a relationship of material interests, such as wages. The reason is, the acquisition of material in their relationship in the midst of the pandemic has also fallen sharply. This study aims to identify Punggawa authority and Sawi compliance that can still exist despite being hit by the Covid-19 pandemic and unfavourable conditions. This study uses a qualitative method with case study analysis. Data sources are divided into two categories, namely primary and secondary sources. Data was collected by using in-depth interviews, observation and documentation techniques. Specifically and tactically, the data analysis technique was carried out following the Miles and Huberman model by reducing data, presenting data and drawing conclusions. The results of this study indicate that the Punggawa authority which is woven into the Punggawa-Sawi relationship in Beba is obtained traditionally. They are not bound by a set of officially announced rules. Sawi's obedience to the retainer was not solely due to material interests. However, their obedience is based more on the characterization of Punggawa because of his generosity and the existence of a familial or kinship relationship between Punggawa and Sawi. This condition makes the relationship between Punggawa and Sawi very close so that it does not waver even in the midst of the Covid-19 pandemic.